2010
DOI: 10.1097/mph.0b013e3181e5e1f1
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Hermansky-Pudlak Syndrome Type 3 in Puerto Rico

Abstract: Background Hermansky-Pudlak Syndrome (HPS) is an autosomal recessive disorder characterized by albinism, mucocutaneous bleeding, and storage of ceroid material in macrophages1. Patients that are not easily identified by physical characteristics (mostly HPS-3 patients) may have hemorrhagic complications with trauma or surgery. Objective To determine the prevalence of HPS-3 in Puerto Rican newborns using DNA pooling technique. Design/Methods Twelve percent of annual Puerto Rican births were tested randomly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Torres and co-workers 24 found that type 3 HPS has an average carrier frequency of 1:85 among Puerto Rican newborns. Our study demonstrated a higher frequency of patients harboring the clinical findings associated to the HPS1 had poorer BCVA, higher incidence of esotropia, total iris transillumination, translucent maculae, and several color deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Torres and co-workers 24 found that type 3 HPS has an average carrier frequency of 1:85 among Puerto Rican newborns. Our study demonstrated a higher frequency of patients harboring the clinical findings associated to the HPS1 had poorer BCVA, higher incidence of esotropia, total iris transillumination, translucent maculae, and several color deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Two separate founder mutations in the HPS1 (10q23) and HPS3 (3q24) genes associated with the Hermansky-Pudlak syndrome have been identified on the island. 14-16 The p.G47D (11q14) mutation associated with Type I-A oculocutaneous albinism in Puerto Rico appeared to have originated from a common founder. 17 In addition, the p.R457Q (11p11) substitution is a common mutation in Puerto Rico and is linked to the otherwise extremely rare genetic prothrombin deficiency disorder.…”
Section: Discussionmentioning
confidence: 99%
“…One in 14,000 individuals of central Puerto Rican descent are estimated to be homozygous for this deletion. The carrier frequency in central Puerto Rico is ~1:32 (Santiago Borrero et al, 2006) and 1:85 in all of Puerto Rico (Torres‐Serrant et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide prevalence of HPS is estimated to be 1–9/1,000,000 (Christensen et al, 2017; Huizing et al, 2000). A few ethnic founder variants occur in HPS genes, in particular in northwest region of Puerto Rico, an estimated 400 individuals are affected (~1/1,800 affected; carrier frequency 1:21) and carry a homozygous 16‐bp duplication in HPS1 (c.1472_1487dup16‐bp; Table 3; Santiago Borrero et al, 2006; Witkop et al, 1990), and in Central Puerto Rico a 3.9‐kb deletion in HPS3 (NM_032383.5(HPS3):c.‐2993_217+692del; Table 5) has an estimated population prevalence of ~1/4,000 (carrier frequency 1:32) in (Anikster et al, 2001; Santiago Borrero et al, 2006; Torres‐Serrant et al, 2010). Other founder variants without frequency estimates have been reported and are discussed elsewhere in this report for each HPS subtype (S. Ito et al, 2005; Oh et al, 1998; Schallreuter et al, 1993; Schreyer‐Shafir et al, 2006).…”
Section: Introductionmentioning
confidence: 99%